2019
DOI: 10.1002/cta.2703
|View full text |Cite
|
Sign up to set email alerts
|

0.6‐V CMOS cascode OTA with complementary gate‐driven gain‐boosting and forward body bias

Abstract: An innovative low-voltage low-power complementary metal-oxidesemiconductor (CMOS) gain boosting approach is presented. It exploits complementary gate-driven gain boosting and adopts forward body bias, resulting in the minimum possible supply requirement of one threshold plus two saturation voltages, without requiring any additional current branch. The solution is also exploited in a rail-to-rail high-performance single-stage cascode operational transconductance amplifier (OTA). Simulations using a 40-nm proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…It can be observed that this design intimates an impressive improvement in FOM SR and g UGB, which allows a more expedient trade-off between speed, power, and load in [28]. This work also exhibits more remarkable small-signal driving ability than [26,[29][30][31][33][34][35] though lower than [27,28,32].…”
Section: Discussion and Comparisonmentioning
confidence: 80%
See 1 more Smart Citation
“…It can be observed that this design intimates an impressive improvement in FOM SR and g UGB, which allows a more expedient trade-off between speed, power, and load in [28]. This work also exhibits more remarkable small-signal driving ability than [26,[29][30][31][33][34][35] though lower than [27,28,32].…”
Section: Discussion and Comparisonmentioning
confidence: 80%
“…Layout area occupation is also identical with low-power reported solutions. Therefore, two traditional figures of merit (FOM) [14,31] shown in Eqs. (49) and (50) , for small-signal performance and largesignal performance evaluation, respectively, are embraced to compare the OTA's dynamic performances under inspection.…”
Section: Discussion and Comparisonmentioning
confidence: 99%
“…FOM1 and FOM2 results of the all circuits are visually illustrated in Figures 14 and 15, respectively. Considering the FOM1 results, it is apparently seen that the proposed circuit outperforms the all other circuits, where the FOM1 score of it is 2816 while the runner-up [27] has a FOM1 of 920. Regarding the FOM2 results, the proposed circuits exhibits quite good performance (the runner-up with 730 FOM2 score) that is close to the best score (1170) achieved by [25].…”
Section: Discussionmentioning
confidence: 94%
“…Over the past decades, their design procedures have faced with the technology scaling mainly imposed by the digital trend predicted by the Moore's law. The reductions of the supply voltage ( DD < 1 V) and of the transistor intrinsic gain ( ∼ 10) pushed the scientific community towards the design of multistage amplifiers where the metric used to evaluate 'speed' performance of OTAs has mainly remained the gain-bandwidth product [1]- [8].…”
Section: Introductionmentioning
confidence: 99%